Pengaruh Tingkat Fear of Missing Out (FoMO) dan Tingkat Pengawasan Orang Tua terhadap Tingkat Kecanduan Penggunaan TikTok pada Remaja - Nadia Gita Aresti; Triyono Lukmantoro; Nurist Surayya Ulfa (Interaksi Online, 2023)
TikTok, a social media platform that is currently growing rapidly, has become a favorite entertainment tool among adolescents. The use of TikTok has positive impacts but can also have a negative impact in the form of TikTok addiction on its users. Fear of missing out may be one of the reasons why adolescents are addicted to TikTok. Thus, parents play a role as gatekeepers to limit the TikTok content that adolescents access. This study aims to determine the influence of fear of missing out (FoMO) level and parental supervision level on the level of addiction to using TikTok in adolescents. The theory in this study used Self-Determination Theory by Ryan and Deci and Parental Mediation Theory by Lynn Clark. In determining the sample, this study used a non-probability sampling technique with a purposive sampling technique. The research population was female and male adolescents with an age range of 15-22 years old in Indonesia who have actively used TikTok in the last three months. The results indicated that fear of missing out (FoMO) level with the level of addiction to using TikTok in adolescents had a significance value of 0.000 where the number was less than 0.05, which means that fear of missing out (FoMO) level, influence the level of addiction to using TikTok in adolescents. Meanwhile, parental supervision level with the level of addiction to using TikTok in adolescents obtained a significance value of 0.231 where the number was more than 0.05, which means it was not significant and it can be argued that parental supervision level had no effect on the level of addiction to using TikTok in adolescents.